Funding the future: safeguarding pediatric health equity through CMS and CHIP - Myers, Carlie N.; Rao, Meera; Bandi, Rishiraj; Densley, Sebastian; Diaz, Daniella; Knecht, Michelle; Sacca, Lea (Frontiers in Public Health, 2025)
Pediatric health disparities remain widespread among marginalized populations, driven by structural racism, poverty, and unequal access to care. While the Centers for Medicare and Medicaid Services (CMS) and the Children's Health Insurance Program (CHIP) have advanced equity in pediatric healthcare, ongoing threats to federal funding jeopardize this progress. This commentary examines five articles, including four CMS-funded interventions that address pediatric health inequities by targeting key social determinants of health (SDoH), including access to care, neighborhood conditions, and insurance coverage. Interventions reviewed include Functional Family Therapy (FFT) for adjudicated youth, a hospital-led asthma management initiative in Ohio, community-based care engagement strategies in disorganized Chicago neighborhoods, and a national policy analysis of CHIP's effectiveness. Across these studies, common themes emerged: community engagement, cross-sector collaboration, and expanded insurance access improved outcomes and reduced costs. Medicaid expansion reduced in-hospital mortality and improved access to rehabilitative care, while CHIP increased preventive service use among near-poor children. However, persistent barriers—including racial and geographic inequities—continue to limit care engagement. While pediatric healthcare research has moved beyond disparity detection, implementation of targeted, evidence-based interventions remains limited. Without sustained investment in CMS and CHIP, the infrastructure supporting equitable pediatric care may erode, exacerbating health gaps for the most vulnerable. Policymakers must prioritize funding and support for initiatives that integrate medical, social, and structural solutions to pediatric health disparities. Strengthening CMS-supported programs is essential not only for improving child health outcomes but also for reducing long-term healthcare costs and advancing pediatric health equity.